2008
DOI: 10.1007/s00339-007-4383-0
|View full text |Cite
|
Sign up to set email alerts
|

Ion irradiation effects on conduction in single-wall carbon nanotube networks

Abstract: We have measured how irradiation by Ar + and N + ions modifies electronic conduction in single-wall carbon nanotube (SWNT) networks, finding dramatically different effects for different thicknesses. For very thin transparent networks, ion irradiation increases localization of charge carriers and reduces the variable-range hopping conductivity, especially at low temperatures. However, for thick networks (SWNT paper) showing metallic conductivity, we find a relatively sharp peak in conductivity as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…58. Several experiments indeed indicate that Young modulus of SWNT bucky paper can be increased due to irradiation, 167,383 as discussed in Sec. V D 2.…”
Section: Mechanical Propertiesmentioning
confidence: 73%
See 1 more Smart Citation
“…58. Several experiments indeed indicate that Young modulus of SWNT bucky paper can be increased due to irradiation, 167,383 as discussed in Sec. V D 2.…”
Section: Mechanical Propertiesmentioning
confidence: 73%
“…This could be interpreted as evidence for irradiation-induced interconnection of nanotubes or functionalization of SWNTs at irradiation-induced defects by various chemical species due to the contact with air accompanied by chemical doping. Further experiments 383 indicated that thermal annealing of tunneling barriers between individual nanotubes by heat released during collisions of energetic ions with the target atoms may be a possible reason for the improvement in conducting properties. By contrast, high energy irradiation of the samples with 23 MeV C 4+ ions did not give rise to any enhancement in conductivity.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Moreover, the present ion beam irradiation technique is useful for defect production in CNTs, which help to alter their structural, optical, magnetic and electrical properties in a highly controlled manner [13,14]. Irradiation-induced changes of buckypaper play a significant role in the case of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…15 It was shown that ion-irradiation-induced double vacancies ͑DVs͒, in comparison to single vacancies ͑SVs͒, strongly reduce the conductivity of metallic tubes. The effects of irradiation in more complicated systems, such as SWNT bundles 16 and films, 17,18 have also been studied and interesting effects such as an increase in the conductance after moderate irradiation dose have been reported. 17 In the transport experiments discussed above, only indirect information on the type of defects can be deduced.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of irradiation in more complicated systems, such as SWNT bundles 16 and films, 17,18 have also been studied and interesting effects such as an increase in the conductance after moderate irradiation dose have been reported. 17 In the transport experiments discussed above, only indirect information on the type of defects can be deduced. Other experimental techniques which are frequently used to asses the amount of defects in carbon nanomaterials such as Raman spectroscopy, [19][20][21] x-ray photo electron spectroscopy, [22][23][24] and electron-spin-resonance method 25,26 provide data which is averaged over many defects.…”
Section: Introductionmentioning
confidence: 99%